Geometry-asymmetric photodetectors from metal–semiconductor–metal van der Waals heterostructures. Issue 12 (21st October 2022) - Fu, Xiao; Li, Tangxin; Li, Qing; Hao, Chunhui; Zhang, Lei; Fu, Dejun; Wang, Jinjin; Xu, Hangyu; Gu, Yue; Zhong, Fang; He, Ting; Zhang, Kun; et al.
Abstract : The geometry-asymmetric metal–semiconductor–metal devices based on the mixed-dimensional vdW heterostructures of SnS layered nanosheets and SnS2 nanoparticles demonstrate great potential in self-rectifying devices and photovoltaic detection. Abstract : The functional diversities of two-dimensional (2D) material devices with simple architectures are ultimately limited by immature doping techniques. An alternative strategy is to use geometry-asymmetric metal–semiconductor–metal (GA-MSM) structures, which enable the basic functions of semiconductor junctions such as rectification and photovoltaics. Here, the mixed-dimensional van der Waals heterostructures (MDvdWHs) based on the separation and self-assembly of p-type SnS layered nanosheets (NSs) and n-type SnS2 nanoparticles (NPs) are obtained using an aqueous phase exfoliation (APE) method. Due to the surface charge transfer doping, the carrier transport mechanism of devices based on MDvdWHs turns from thermionic field emission (TFE) to thermionic emission (TE), with the rectification factor ( I forward / I reverse ) changing from 0.7 to 3. To further illustrate the experimental results, the generic current transport models of GA-MSM devices have been established based on the TE and TFE mechanisms in which the TE and TFE mechanisms lead to opposite rectification phenomena in good agreement with the experimental results. The GA-MSM devices show a photovoltaic effect with a high responsivity of 35 A W −1 and detectivity of 3.4 × 10 11 cm Hz 1/2 W −1 . This study not only provides a novel strategy to design photovoltaic devices with MDvdWHs, but more importantly, we have established fundamental models for the rectification behavior of GA-MSM devices.